2013
DOI: 10.1890/es12-00236.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation of event related N2O and CH4 emissions during fertigation in a California almond orchard

Abstract: Abstract. Nitrogen fertilizer applied to soil is the primary source of the greenhouse gas (GHG) nitrous oxide (N 2 O). The assessment of N 2 O emissions, or net fluxes of the GHG methane (CH 4 ), are lacking for upland, arid agricultural ecosystems worldwide. In California, where rates of application for nitrogen (N) can exceed 300 kg per hectare for N-intensive fruit and nut crops (.2 million acres), liquid N fertilizers applied through microirrigation systems (fertigation) represent the predominant method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 56 publications
5
34
2
Order By: Relevance
“…However, the impact of intensive N management on N 2 O and CH 4 fluxes in upland orchards is not well understood because quantitative information on this topic is scarce. Reported N 2 O emissions from orchard soils range from 0.5 to 8.6 kg N ha −1 year −1 and vary in response to climate, land use, and management practices [14,[31][32][33][34][35]. These observations are similar to most cropland-related N 2 O emissions reviewed in Stehfest and Bouwman [20].…”
Section: Introductionmentioning
confidence: 57%
“…However, the impact of intensive N management on N 2 O and CH 4 fluxes in upland orchards is not well understood because quantitative information on this topic is scarce. Reported N 2 O emissions from orchard soils range from 0.5 to 8.6 kg N ha −1 year −1 and vary in response to climate, land use, and management practices [14,[31][32][33][34][35]. These observations are similar to most cropland-related N 2 O emissions reviewed in Stehfest and Bouwman [20].…”
Section: Introductionmentioning
confidence: 57%
“…Several recent studies conducted in orchard systems have also reported that concentrations of extractable NO 3 tend to be higher in soils under drip than microsprinker irrigation (Alsina et al 2013; Kadyampakeni **** ** **** **** **** I × A n s n s n s n s n s…”
Section: Discussionmentioning
confidence: 95%
“…Webb) orchard suggests that differences in NO 3 -N IER between irrigation treatments are not caused by losses of mineral N via denitrification (Alsina et al 2013). Instead, greater water-filled pore spaces in the wetted bulb of soil beneath drippers may support higher rates of N mineralisation; under microsprinklers, higher evaporative losses from the soil surface tend to reduce soil moisture, which may lead to lower rates of N mineralisation (Alsina et al 2013). Furthermore, uniformly wet conditions, as were observed under drip irrigation, may support greater rates of cumulative N mineralization than repeated drying-wetting cycles (Mikha et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations